Students' Perceptions of Madrasah Teacher Education Ibtidaiyah (PGMI) and Religious Education Islam (PAI) on the Role of Lecturer’s Academic Advisor in the Time of The Covid-19 Pandemic - Noor Isna Alfaein; Ending Bahruddin; Khaidir Fadil (AS-SABIQUN, 2022)
Study this aim to describe how students perceive Madrasah Ibtidaiyah and Islamic Religious Education students regarding the role of academic supervisors during the COVID-19 pandemic. Type study this is study qualitative with the use method intended descriptive to describe how the perceptions of PGMI and PAI students towards the role of academic supervisors. In obtaining research data, researchers use two sources, namely primary and secondary data. The primary data sources used by the informants main are students of PGMI and PAI class of 2019 While the secondary data used covers journals and books. Data collection techniques used are interviews and questionnaires distributed to students. Data analysis techniques consist of three plot activities interactive and ongoing Keep going continuously until completed, namely: 1) Data reduction. 2) Data presentation. And, 3) Interesting conclusion. The results of the research show that students' perceptions of the role of academic supervisors are good, this is evidenced by the good perceptions of students in several indicators. but 3 indicators must be immediately corrected by the role of academic guiding lecturers, namely improving the quality of academic guidance in the field of worship practices, then academic supervisors must reactivate classical meetings at least once a month. As well to academic mentoring lecturers are required to take the time to be easily found by their guidance students.